Mentoring in Research-Practice Partnerships: Toward Democratizing Expertise - María Paula Ghiso; Gerald Campano; Emily R. Schwab; Dee Asaah; Alicia Rusoja (SAGE Publishing, 2019)
Reconceiving relationships between universities, schools, and community organizations through research-practice partnerships, and building capacity for partnership work, necessarily entails rethinking the mentorship of graduate students. In this article, we describe our findings on what mentorship looks like in a now 9-year RPP focusing on educational equity through participatory approaches. The authors include the two project principal investigators and three doctoral students who participated at different stages of the project, one of whom is now a faculty member. In our analysis, we identify dimensions of a more horizontal form of mentorship, involving qualities and skills that extend beyond traditional practices of academic apprenticeship: universalizing who is an intellectual, cultivating community responsiveness, implementing collective structures and protocols, and constructing a shared vision. Our findings shift conceptions of mentorship from individual apprenticeship into a narrowly defined discipline to a collective undertaking that aims to democratize expertise and enact a new vision of the public scholar.